Percutaneous vertebroplasty by two-step fluoroscopy: a treatment for osteoporotic compression fractures of thoracic vertebrae in older adults - Jianzhong Ge; Kuisheng Chen; Peng Xu; Zhiling Zhang; Kai Wang; Tao Zhang; Xin Dong; Zhigang Kang; Yizhou Ge; Feng Chang (BMC Musculoskeletal Disorders)
Abstract Objective This study aimed to evaluate the clinical efficacy of percutaneous vertebroplasty (PVP) performed with a two-step fluoroscopy technique for treating thoracic osteoporotic vertebral compression fractures (OVCFs) in older patients. Methods A retrospective analysis was conducted on clinical and imaging data from 48 patients diagnosed with thoracic OVCFs, who underwent treatment with percutaneous vertebroplasty(PVP) utilizing a two-step fluoroscopy technique at Yangquan First People’s Hospital between January 2019 and January 2022. The study assessed the clinical efficacy of this procedure by analyzing Visual Analog Scale(VAS) scores, Cobb angle values, and vertebral height measurements before surgery and at 2 days, 3 months, 6 months, and 12 months postoperatively. Results Before treatment, the mean VAS score of patients was 7.5 ± 0.6. Subsequently, at 2 days, 3 months, 6 months, and 12 months after the procedure, these mean scores decreased to 2.3 ± 0.6, 2.2 ± 0.5, 2.2 ± 0.4, and 2.0 ± 0.3, respectively. This decline was statistically significant (P < 0.05) compared to the preoperative VAS score. The preoperative Cobb angle was 12.1° ± 0.9°, and the Cobb angle values at the corresponding time points were 12.2° ± 0.8°, 12.3° ± 1.1°, 12.3° ± 1.0°, and 12.2° ± 0.9°. Initially, the mean height of the vertebral body in these patients was 17.38 ± 1.56 mm. Postoperatively, at 2 days, 3 months, 6 months, and 12 months, these values were 19.30 ± 1.81 mm, 19. 12 ± 1.60 mm, 19.00 ± 1.45 mm, and 19.00 ± 1.20 mm, respectively. No significant difference was observed between postoperative and preoperative Cobb angle and vertebral height (P > 0.05). Conclusion Percutaneous vertebroplasty using a two-step fluoroscopy method not only has the therapeutic effect of traditional surgical methods, reducing pain from thoracic vertebral compression fractures in the elderly and enhancing their quality of life and mobility, but also streamlines the intraoperative fluoroscopy procedure. This method stand as an effective approach for managing osteoporotic compression fractures of the thoracic vertebrae in elderly.